The Influence of TAM Variables and Financial Literacy on QRIS Payment Decisions with Interest as an Intervening Variable (Study on Semarang State Polytechnic Students) - Edi Wijayanto,; Muhammad Rois,; Theresia Tyas Listyani,; Sri Widiyati,; Manarotul Fatati, (International Journal of Scientific Research and Management (IJSRM), 2024)
The rapid evolution of digital technology, especially in the digital economy and payment sector, has driven the widespread adoption of digital payment services utilizing QR Codes. The Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia and the Indonesian Payment System Association (ASPI) on August 17, 2019, serves as the national QR code standard, facilitating QR code-based payments across Indonesia. QRIS presently allows the acceptance of payment applications, whether from banks or non-banks, at various establishments. This study, involving 370 students from a population of 6,128, utilizes the Structural Equation Model (SEM) for analysis, demonstrating a robust fit with a GFI value surpassing 0.913. The findings reveal that TAM variables—perceived ease of use, perceived usefulness, perceived enjoyment, and financial literacy—significantly influence decision of QRIS payment through interest in adopting digital payments as an intervening variable, supported by probability values below 5%